Propuesta de factibilidad para la implementación de una metalmecánica en la parroquia de Tambillo - Cueva Chicaiza, Marco Vinicio (2022)
This study aims to determine the feasibility of installing a metalworking micro-enterprise in Tambillo parish, which satisfies the demand for metalworking products in that place, which contributes to the economic development of the parish, through a market, technical and financial study. The market study made it possible to verify the current situation of the parish, establishing the opportunities, threats, and demand to be satisfied by applying surveys to the population to know their requirements and needs; also, interviews were applied to the competition to formulate positioning strategies in the market. The technical study determined the micro-enterprise position, the organization, and their marketing strategies were also established to achieve correct organizational management. Finally, the economic study in which the feasibility and profitability of the project was demonstrated through financial analysis tools.